2018
DOI: 10.3389/fendo.2018.00596
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Intake, Meat Consumption, and Dairy Consumption in the Year Preceding Pregnancy and During Pregnancy and Their Associations With the Risk of Gestational Diabetes Mellitus: A Prospective Cohort Study in Southwest China

Abstract: Background: Gestational diabetes mellitus (GDM) has become a public health problem in China.Objective: To examine the association of dietary protein intake before and during pregnancy with the risk of GDM.Design: Dietary intake before pregnancy and during the first and second trimesters of pregnancy was assessed using food frequency questionnaires in a prospective cohort of pregnant women. To screen GDM, participants underwent an OGTT test during 24–28 weeks of gestation. Cox proportional hazards were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 70 publications
3
36
0
1
Order By: Relevance
“…It was corroborated by a prospective study conducted in a cohort of Chinese women. The study showed that higher branched-chain amino acid content consumed with meat and dairy products in the second part of pregnancy was associated with the increase in the risk of gestational diabetes mellitus by approximately 95% [30]. According to some authors, whey proteins, by modifying gene expression, may affect glucose metabolism, also by its increased use in the liver.…”
Section: Dairy Products and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…It was corroborated by a prospective study conducted in a cohort of Chinese women. The study showed that higher branched-chain amino acid content consumed with meat and dairy products in the second part of pregnancy was associated with the increase in the risk of gestational diabetes mellitus by approximately 95% [30]. According to some authors, whey proteins, by modifying gene expression, may affect glucose metabolism, also by its increased use in the liver.…”
Section: Dairy Products and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Although no studies to our knowledge have assessed the associations between protein quality and maternal insulin sensitivity measures, various studies have noted associations with the RR of GDM (29, 49–51). Nonetheless, findings are not consistent in that most of these studies found an association with only total animal protein consumption (29, 49, 50), whereas 1 study found that both total animal and total plant protein intakes were related (51). Although this is convincing evidence, any noted effects of animal protein sources on the RR of GDM may be limited to the specific type of animal protein source (29, 49, 51).…”
Section: Current Status Of Knowledgementioning
confidence: 76%
“…37 However, these energy intakes stemmed more from protein and fat and less from carbohydrates, which may be because animal foods are thought to have better nutritional quality for pregnant women in Chinese culture. Both protein intake and animal protein intake increased the risk of GDM among NPGSC population, 24 and this was most pronounced for the time window closest to GDM diagnosis. Moreover, since China is experiencing a rapid diet and lifestyle transition (eg high energy intake and sedentary lifestyles), 38 more young women tend to enter pregnancy with excessive body weight.…”
Section: Discussionmentioning
confidence: 96%
“…Higher dietary intakes of total protein and animal protein in midpregnancy were associated with an increased risk of GDM. 24 In addition, higher energy intake in the 3rd trimester 12 was associated with increased risk of excessive GWG. Adequate energy density based on food and milk in the 3rd trimester decreased the risk of excessive GWG.…”
Section: The Impact Of Dietary Factors On Maternal Healthmentioning
confidence: 99%
See 1 more Smart Citation